Semaphorin-Plexin Signaling Guides Patterning of the Developing Vasculature - Torres-Vázquez, Jesús; Gitler, Aaron D; Fraser, Sherri D; Berk, Jason D; Van N. Pham; Fishman, Mark C; Childs, Sarah; Epstein, Jonathan A; Weinstein, Brant M (Developmental cell, 2004)
Major vessels of the vertebrate circulatory system display evolutionarily conserved and reproducible anatomy, but the cues guiding this stereotypic patterning remain obscure. In the nervous system, axonal pathways are shaped by repulsive cues provided by ligands of the semaphorin family that are sensed by migrating neuronal growth cones through plexin receptors. We show that proper blood vessel pathfinding requires the endothelial receptor PlexinD1 and semaphorin signals, and we identify mutations in plexinD1 in the zebrafish vascular patterning mutant out of bounds. These results reveal the fundamental conservation of repulsive patterning mechanisms between axonal migration in the central nervous system and vascular endothelium during angiogenesis.